2021
DOI: 10.1111/jth.15191
|View full text |Cite
|
Sign up to set email alerts
|

The ADAMTS13‐von Willebrand factor axis in COVID‐19 patients

Abstract: Background Severe coronavirus disease 2019 (COVID‐19) is characterized by an increased risk of thromboembolic events, with evidence of microthrombosis in the lungs of deceased patients. Objectives To investigate the mechanism of microthrombosis in COVID‐19 progression. Patients/Methods We assessed von Willebrand factor (VWF) antigen (VWF:Ag), VWF ristocetin‐cofactor (VWF:RCo), VWF multimers, VWF propeptide (VWFpp), and ADAMTS13 activity in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

41
233
0
6

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(293 citation statements)
references
References 45 publications
(94 reference statements)
41
233
0
6
Order By: Relevance
“…This has been evidenced by markedly reduced clot lysis at 30 min via thromboelastography (TEG) in critically-ill patients with COVID-19 18 . Ex vivo evaluation of COVID-19 plasma also noted a prolonged clot lysis time, which was more pronounced among critically-ill COVID-19 patients 19 . Furthermore, a case series demonstrated that 11 of 21 COVID-19 patients who underwent rotational thromboelastometry in an intensive care unit met the criteria for fibrinolytic shutdown; 9 of those 11 patients developed thrombosis during their hospitalization 20 .…”
Section: Introductionmentioning
confidence: 88%
“…This has been evidenced by markedly reduced clot lysis at 30 min via thromboelastography (TEG) in critically-ill patients with COVID-19 18 . Ex vivo evaluation of COVID-19 plasma also noted a prolonged clot lysis time, which was more pronounced among critically-ill COVID-19 patients 19 . Furthermore, a case series demonstrated that 11 of 21 COVID-19 patients who underwent rotational thromboelastometry in an intensive care unit met the criteria for fibrinolytic shutdown; 9 of those 11 patients developed thrombosis during their hospitalization 20 .…”
Section: Introductionmentioning
confidence: 88%
“…It has not been fully elucidated yet whether this hypercoagulable state depends on a direct endothelial damage inflicted by the virus or represents a consequence of cytokine storm precipitating the onset of SIRS [ 66 ]. The blood coagulation activation in COVID-19, also substantiated by elevated levels of fibrinogen, Von Willebrand factor activity and factor VIII, seems not meet the criteria for disseminate intravascular coagulation, as platelet count and prothrombin time have been mostly reported within normal ranges, or just slightly increased, in these patients [ 67 , 68 ].…”
Section: Coagulation Abnormalities and Pulmonary Embolismmentioning
confidence: 99%
“…Compatible with severe endothelial damage, several authors noted marked elevations of Von Willebrand factor activity (VWF:act), VWF antigen (VWF:Ag) and factor VIII clotting activity (FVIII:C) in COVID-19 patients [ 7 , 8 , 11 , [17] , [18] , [19] , [20] ] and some found low normal or mildly decreased ADAMTS13 (A Disintegrin And Metalloprotease with ThromboSpondin type 1 motif, number 13) activity [ 8 , 9 , 11 , [18] , [19] , [20] ]. The VWF:Ag/ADAMTS13 activity ratio was strongly elevated in these studies [ 8 , 11 , 18 , 20 ].…”
mentioning
confidence: 99%
“…This imbalance of a markedly increased VWF and moderately decreased ADAMTS13 levels with an elevated VWF/ADAMTS13 ratio is suggested to represent a «consumption» of ADAMTS13 by the massively increased VWF and proposed to contribute to the pulmonary microthrombi formation [ 21 ]. The authors note that in contrast to the disease thrombotic thrombocytopenic purpura (TTP), defined by a very severe autoantibody-mediated or congenital deficiency of the ADAMTS13 [ 22 , 23 ], the hallmarks of severe thrombocytopenia and microangiopathic hemolytic anemia are lacking in almost all COVID-19 patients [ 7 , 8 , 20 ]. Also, the thrombi of the pulmonary microcirculation have mostly been reported as predominantly “fibrinous” [ [14] , [15] , [16] ], even though Fox et al suggested the presence of platelets and VWF in the microthrombi of pulmonary alveolar capillaries by immunostaining [ 24 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation